Soursop leaf extract as biodiesel antioxidant and the effect on automotive diesel engine performance. Issue 1 (March 2021) - Widjanarko, D; Azhar, S; Megawati,
Abstract: This study aims to determine the effect of soursop leaf extraction as biodiesel antioxidants on the torque and power of diesel engines. Fuels were made by mixing the soursop leaf antioxidants of 50 ppm, 100 ppm and 150 ppm, to 1 litre of B30 fuel. The fuels were applied to diesel-engine vehicles. Diesel engine performance was tested by a chassis dynamometer. The results showed that the use of an antioxidant mixture of 50 ppm, 100 ppm, and 150 ppm in biodiesel caused a decrease in torque of 12.61%; 17.37%; 16.69% respectively, and the power was also decreased of 12.34%; 18.16% and 16.37% compared to biodiesel without antioxidant mixture.